Effect of culturing lactic acid bacteria with varying skim milk concentration on bacteria survival during heat treatment. (April 2021) - Suo, Xiangshu; Huang, Song; Wang, Juan; Fu, Nan; Jeantet, Romain; Chen, Xiao Dong
Abstract: Four lactic acid bacteria (LAB) strains were cultured in reconstituted skim milk with different solids contents to compare the thermotolerance of resulting cultures. As milk concentration was increased from 5 to 30 wt%, the population of non-lactose-fermenting strains increased by around 1 log at stationary growth phase. High solids milk maintained relative stable pH (ΔpH<0.5) when fermented with a lactose-fermenting strain, compared to a drastic pH drop by 1.35 in low solids milk. All four strains cultured in 20 or 30 wt% milk demonstrated significant improvements in cell survival (remaining viability > 10 8 CFU/mL) and growth capability after heat treatment at 65 °C for 10 min, indicating a general thermoprotective effect irrespective of metabolic pathways. Besides cellular response to high osmolality during bacterial growth, we proposed that the increased concentration of protective dairy components and the increased viscosity and thermal resistance of culture medium also contributed to the excellent thermotolerance. Highlights: LAB grown in 20%–30% skim milk showed better thermotolerance than that in 5% milk. The improved thermotolerance was general for four strains with different metabolism. After 10-min heating at 65 °C, residual viability of each strain was > 10 8 cfu/mL. Cellular stress response may be activated when grown in high solids milk. The rich protective agents and high viscosity of milk medium may protect cells.